2007
DOI: 10.1007/s00438-007-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of EamaT1, a member of maT family of transposable elements from the earthworm Eisenia andrei (Annelida, Oligochaeta)

Abstract: The maT family is a unique clade within the Tc1-mariner superfamily, and their distribution is to date known as being limited to invertebrates. A novel transposon named EamaT1 is described from the genome of the earthworm Eisenia andrei. The full sized EamaT1 was obtained by degenerate and inverse PCR-based amplification. Sequence analysis of multiple copies of the EamaT1, which consisted of 0.9 and 1.4 kb elements, showed that the consensual EamaT1 with inverted terminal repeats (ITRs) of 69 bp was 1,422 bp l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…In addition, ChIP results showed that Twist binds to the region of ROR1 promoter from -802 to -402 (fragment 3) and from -6 to 399 (fragment 5); the Vimentin and GAPDH promoter were used as positive and negative controls, respectively ( Figure 2 B-C ). We found that there was one E-box motif in fragment 3 ( Figure S3 A ) and two E-box elongated motifs 26 , 27 in fragment 5 (EL1 and EL2) ( Figure 2 D ). Intriguingly, the promoter activity of ROR1 marginally affected by mutating E-box in fragment 3 ( Figure S3 B ); however, its activity was greatly reduced by mutating either one or both of the two elongated E-box motifs in fragment 5 ( Figure 2 E ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, ChIP results showed that Twist binds to the region of ROR1 promoter from -802 to -402 (fragment 3) and from -6 to 399 (fragment 5); the Vimentin and GAPDH promoter were used as positive and negative controls, respectively ( Figure 2 B-C ). We found that there was one E-box motif in fragment 3 ( Figure S3 A ) and two E-box elongated motifs 26 , 27 in fragment 5 (EL1 and EL2) ( Figure 2 D ). Intriguingly, the promoter activity of ROR1 marginally affected by mutating E-box in fragment 3 ( Figure S3 B ); however, its activity was greatly reduced by mutating either one or both of the two elongated E-box motifs in fragment 5 ( Figure 2 E ).…”
Section: Resultsmentioning
confidence: 92%
“…However, mutations on either one or both of two elongated E-box motifs in the -6 to 399 (fragment 5) region could abrogate the Twist-induced ROR1 promoter reporter activity. Previous studies identified a non-canonical E-box motif, which is called E-box elongated CANNNTG, that may also serve as a potential DNA-binding site 26 , 27 . Although there is no report on whether Twist can recognize this E-box elongated motif, our evidences showed that mutations in this motif can abrogated Twist-induced ROR1-promoter activity, suggesting that Twist may recognize this E-box elongated motif on the gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The mariner and Tc1 elements were found in D. mauritiana (Jacobson et al, 1986) and the nematode Caenorhabditis elegans (Emmons et al, 1983), respectively, and related elements are known to occur in diverse taxa, including planarians (Garcia-Fernandez et al, 1995), annelids (Jee et al, 2007), vertebrates (Smit and Riggs, 1996), plants (Jarvik and Lark, 1998) and fungi (Langin et al, 1995). Manifestation of such a wide distribution leads to the inference that elements of this family require no or few factors produced from host cells for their transposition reaction.…”
Section: Introductionmentioning
confidence: 99%
“…的 Tdr1 [27] 、泥鳅(Misgurnus mizolepis)的 MMTS [28] 和蚯 蚓(Eisenia Andrei)的 EamaT1 [29] 等具有不同元件. 根 据转座子元件间序列比对, 可推测出 LTEs 的一致性 序列.…”
Section: 结构特征unclassified